The Functions and Mechanisms of Tendon Stem/Progenitor Cells in Tendon Healing - Jingwei Lu; Hui Chen; Kexin Lyu; Li Jiang; Yixuan Chen; Longhai Long; Xiaoqiang Wang; Houyin Shi; Sen Li (Hindawi Limited, 2023)
Tendon injury is one of the prevalent disorders of the musculoskeletal system in orthopedics and is characterized by pain and limitation of joint function. Due to the difficulty of spontaneous tendon healing, and the scar tissue and low mechanical properties that usually develops after healing. Therefore, the healing of tendon injury remains a clinical challenge. Although there are a multitude of approaches to treating tendon injury, the therapeutic effects have not been satisfactory to date. Recent studies have shown that stem cell therapy has a facilitative effect on tendon healing. In particular, tendon stem/progenitor cells (TSPCs), a type of stem cell from tendon tissue, play an important role not only in tendon development and tendon homeostasis, but also in tendon healing. Compared to other stem cells, TSPCs have the potential to spontaneously differentiate into tenocytes and express higher levels of tendon-related genes. TSPCs promote tendon healing by three mechanisms: modulating the inflammatory response, promoting tenocyte proliferation, and accelerating collagen production and balancing extracellular matrix remodeling. However, current investigations have shown that TSPCs also have a negative effect on tendon healing. For example, misdifferentiation of TSPCs leads to a "failed healing response," which in turn leads to the development of chronic tendon injury (tendinopathy). The focus of this paper is to describe the characteristics of TSPCs and tenocytes, to demonstrate the roles of TSPCs in tendon healing, while discussing the approaches used to culture and differentiate TSPCs. In addition, the limitations of TSPCs in clinical application and their potential therapeutic strategies are elucidated.